Jatrophane diterpenes from Euphorbia guyoniana are new potent inhibitors of atrial GIRK channels. Issue 37 (15th September 2016) - Kúsz, Norbert; Orvos, Péter; Csorba, Attila; Tálosi, László; Chaieb, Mohammad; Hohmann, Judit; Rédei, Dóra
Abstract: Two new jatrophane diterpenes, guyonianin G (1 ) and H (2 ), were isolated from the methanol extract of Euphorbia guyoniana Boiss. & Reut. The structures were established by means of a combined spectroscopic data analysis, including HRESIMS, and 1D- and 2D-NMR techniques. The isolated compounds were not identical with the previously reported compounds of E. guyoniana, indicating the high chemical diversity of this species. Electrophysiological effects of guyonianin G (1 ) and H (2 ), together with four jatrophane diterpenes previously isolated from Euphorbia mongolica, Euphorbia serrulata and Euphorbia salicifolia were investigated on stable transfected HEK–GIRK1/4 (Kir3.4) cell lines using automated patch clamp equipment. Significant blocking activity on GIRK channel was exerted by diterpenes1 –5, but no blocking activity of6 was detected. The common jatropha-6(17), 11 E -diene, guyonianin G (1 ) with three large ester groups (one benzoyl and two isobutanoyl groups) was the most active (70% at 10 μM) GIRK channel inhibitory compound. Graphical abstract: